Promoting Extracellular Electron Transfer of Shewanella oneidensis MR-1 by Optimizing the Periplasmic Cytochrome c Network - Sun, Weining; Lin, Zhufan; Yu, Qingzi; Cheng, Shaoan; Gao, Haichun (Frontiers in Microbiology, 2021)
The low efficiency of extracellular electron transfer (EET) is a major bottleneck for Shewanella oneidensis MR-1 acting as an electroactive biocatalyst in bioelectrochemical systems. Although it is well established that a periplasmic c-type cytochrome (c-Cyt) network plays a critical role in regulating EET efficiency, the understanding of the network in terms of structure and electron transfer activity is obscure and partial. In this work, we attempted to systematically investigate the impacts of the network components on EET in their absence and overproduction individually in microbial fuel cell (MFC). We found that overexpression of c-Cyt CctA leads to accelerated electron transfer between CymA and the Mtr system, which function as the primary quinol oxidase and the outer-membrane electron hub in EET. In contrast, NapB, FccA and TsdB in excess severely impaired EET, reducing EET capacity in MFC by more than 50%. Based on the results from both strategies, a series of engineered strains lacking FccA, NapB, and TsdB in combination while overproducing CctA were tested for a maximally optimized c-Cyt network. A strain depleted of all NapB, FccA and TsdB with CctAverproduction achieved the highest maximum power density in MFCs (436.5 mW/m2), ∼3.62-fold higher than that of WT. By revealing that optimization of periplasmic c-Cyt composition is a practical strategy for improving EET efficiency, our work underscores the importance in understanding physiological and electrochemical characteristics of c-Cyts involved in EET.